2005
DOI: 10.1007/s10522-005-4906-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Anti-Aging Caloric Restrictions on Carbonyl and Heat Shock Protein Levels and Expression

Abstract: Heat shock proteins (Hsps) are induced by stressful stimuli and have been shown to protect cells and organs from such stresses both in vitro and in vivo, and play a positive role in lifespan determination. An attenuated response to stress is characteristic of senescence and no Hsp induction is observed upon exposure to stress and no protective effect of a mild stress is observed in cells from aged individuals. The artificial over-expression of Hsps, can produce a protective effect against a variety of damaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
6
26
0
Order By: Relevance
“…Indeed, Pietrangelo et al [59] have clearly shown an increased percentage of fast, white muscle fibres in CFS patients. In addition to these findings in different muscle types, several human studies have demonstrated an attenuated HSP response to stress in elderly individuals in relation to enhanced oxidative stress [60,61]. It is tempting to speculate that the accumulation of two or more stressors might be the cause of a lowering of spontaneous and induced HSP production.…”
Section: Heat Shock Proteins In Cfs Patientsmentioning
confidence: 89%
“…Indeed, Pietrangelo et al [59] have clearly shown an increased percentage of fast, white muscle fibres in CFS patients. In addition to these findings in different muscle types, several human studies have demonstrated an attenuated HSP response to stress in elderly individuals in relation to enhanced oxidative stress [60,61]. It is tempting to speculate that the accumulation of two or more stressors might be the cause of a lowering of spontaneous and induced HSP production.…”
Section: Heat Shock Proteins In Cfs Patientsmentioning
confidence: 89%
“…A number of recent microarray studies have found that metabolic genes are disproportionately influenced by environmental stress, senescence, and inbreeding treatments (Girardot et al 2004;Landis et al 2004;Wang et al 2004;Englander 2005;Kristensen et al 2005). At a broad level, the role of metabolism in these processes may account for interactions between environmental stress and the magnitude of inbreeding depression (Crnokrak and Roff 1999;Keller and Waller 2002;Armbruster and Reed 2005), quantitative genetic correlations between stress resistance and extended life span Rose et al 1992;Force et al 1995;Zwaan et al 1995;Chippindale et al 1998;Norry and Loeschcke 2003), and similarities among the molecular effects of stress, inbreeding, and aging treatments observed in several species (Chen et al 2002;Brunet et al 2004;Lamming et al 2004;Colotti et al 2005;Kristensen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…With aging, the HSP response to stress is blunted while the propensity to develop diabetes increases. 50 Hypertension is associated with insulin resistance and impaired insulin signaling. 51 Angiotensin II increases inflammatory cytokines, particularly NF-B, which can impair insulin signaling.…”
Section: Agents or Conditions That Alter Hsps And Diabetesmentioning
confidence: 99%